Participatory retrofitting of school playgrounds: Collaboration between children and university students to develop a vision. (September 2018) - Menconi, M.E.; Grohmann, D.
Highlights: The paper shows the great values of shared projects between university and elementary school students. The paper shows the importance of the school open spaces as extensions of the classrooms. The paper presents a participatory design process involving 288 children and their teachers. Children can develop complex design projects within a participation process. A fun game is developed to help children understand the concept of scale. Abstract: Children participation in the design of urban open spaces is a well-known phenomenon, but a gap still remains between theory and practice. In particular, school playgrounds often suffer from standardization of design that fails to reflect the different functions and the different services required to achieve full children development. Starting from these considerations, the paper aims (i) to develop a transferable method to retrofit school playgrounds, building alliances between universities, elementary schools, and the public administration, (ii) to present the main results of this method applied to an Italian school with 288 children (aged 5–10) in a six-month process and (iii) to interpret the previous results in the light of an analytic frame to outline some key finding useful to manage participatory processes to retrofit school playgrounds. The method provides useful considerations on the value offered by collaborative projects between universities and elementary schools. Generally, the case study shows the transferability of the method offering a significant support to playworkers to develop satisfactory, child-friendly design choices. Observing the Italian children's point of view, the paper shows that they identify the school playground with green spaces and traditional play setting, at the same time, they ask for multifunctional school playgrounds that allow for considering school's open spaces as extensions of the classroom.